2012
DOI: 10.1074/jbc.m112.392530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cardiomyocytes Differentiation of Mouse Embryonic Stem Cells by CD38/cADPR/Ca2+ Signaling Pathway

Abstract: Background: The role and mechanism of cADPR, an endogenous Ca2+-mobilizing nucleotide, in cardiomyogenesis remain to be determined.Results: We found that inhibition of the cADPR cascade facilitated cardiomyocyte differentiation of mouse ES cells.Conclusion: The CD38-cADPR-Ca2+ signaling pathway antagonizes the cardiomyocyte differentiation of mouse ES cells.Significance: Inhibition of cADPR signaling should provide a good approach to enrich functional cardiomyocytes from ES cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…S2C). Similar results have also been observed in several other mouse ESC lines [14]. Taken together, these data suggest that CD38 is not essential for the pluripotency and self-renewal of mouse ESCs.…”
Section: Characterization Of the Cd38/cadpr/ca 21 Signaling In Esc-desupporting
confidence: 76%
See 3 more Smart Citations
“…S2C). Similar results have also been observed in several other mouse ESC lines [14]. Taken together, these data suggest that CD38 is not essential for the pluripotency and self-renewal of mouse ESCs.…”
Section: Characterization Of the Cd38/cadpr/ca 21 Signaling In Esc-desupporting
confidence: 76%
“…Previously, we found that the expression of CD38 was increased during the differentiation of ESCs initiated by EB formation, and the final EB culture was a heterogenous mixture of various cell types and the proportion of neural lineage among them is low [14]. Interestingly, the expression of CD38 was markedly decreased during the differentiation of ESCs initiated by monolayer adherence culture (Fig.…”
Section: Characterization Of the Cd38/cadpr/ca 21 Signaling In Esc-dementioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis and the hydrolysis of both NAADP and cADPR, are catalyzed by cluster of differentiation 38 (CD38) in mammalian cells. CD38 has also been detected in mouse D3, R1 and Sox1-GFP 46C ESCs [24] [25]. In addition to TRPC1 and TRPC2, other types of non-selective cation channels, such as TRPC3 and TRPC7 (unpublished This is the Pre-Published Version data) as well as transient receptor potential vanilloid 1 (TRPV1) [26] are also expressed in mouse Sox1-GFP 46C and D3 ESCs.…”
mentioning
confidence: 98%